The Role of Layout in Architectural Design - Eldorjon Erkinjon ogli Cholponov; Zafarbek Erkinovich Matniyazov (International Journal on Orange Technologies, 2022)
The problem of increasing the efficiency of the process of designing spatially developed objects of architecture and urban planning through the rational use of modern materials, technologies and technical means is considered. In particular, the foreign experience of using rapid prototyping technologies in architectural design is analyzed. It is proposed to use a compact technology of rapid prototyping for the introduction of automated prototyping in architectural and urban design practice.